Relación entre la seguridad ciudadana y el gasto público en orden público y seguridad en el departamento de Loreto durante el periodo 2013–2024 - Gomez Palacios, Santos William (2025)
This research analyzes the relationship between public spending on law and order and the indicators of citizen security in the department of Loreto during the period 2013–2024. The study was conducted under a quantitative, non experimental, longitudinal, and correlational approach, using secondary data obtained from official sources such as the Ministry of Economy and Finance (MEF), the National Institute of Statistics and Informatics (INEI), and the National Police of Peru (PNP). Based on a total of 48 quarterly observations, descriptive statistical analysis and Spearman correlation tests were applied to test the proposed hypotheses. The results showed that, in general terms, there is a positive and significant relationship between public spending on security and citizen security levels in Loreto, which validates the general hypothesis. However, when examining the specific hypotheses, it was found that budgetary spending did not reduce homicides or property crimes; rather, both increased in parallel with investment, reflecting spending that was reactive rather than preventive. On the other hand, it was confirmed that budget execution was positively linked to the availability of police officers. These findings demonstrate that public spending is necessary but not sufficient to improve citizen security, making it essential to optimize its efficiency and strategic orientation.